Adverse Events During Invasive EEG Recordings - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers in the Department of Paediatric Neurosurgery and Epilepsy Unit, Great Ormond Street Hospital, London, UK analyzed the hospital charts of 95 children operated on between 1995 and 2009 for medication-resistant focal epilepsy and requiring presurgical intracranial monitoring of the EEG.